PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI PADA GENERASI MUDA DI KELURAHAN BENJALA KECAMATAN BONTOBAHARI KABUPATEN BULUKUMBA - Nur, Sulistiwati; Anwar, Anwar; Aslam, Annisa Paramaswary (IAIN Parepare, 2025)
This study aims to analyze the influence of financial literacy on investment decisions among young people in Benjala Village, Bontobahari District, Bulukumba Regency. Financial literacy in this study includes basic financial knowledge, income and expenditure management, risk understanding, and the use of financial technology. Investment decisions cover understanding investment products, readiness to face risks, and the suitability of investment decisions with personal financial goals.This research uses a quantitative method with an associative approach. Data were obtained through questionnaires distributed to 360 young respondents in Benjala Village, using purposive sampling technique. The data were analyzed using descriptive analysis and simple linear regression to determine the influence of financial literacy on investment decisions.The results show that the financial literacy of young people in Benjala Village is relatively good. Most respondents have adequate understanding of personal financial management and risk, although some still lack in utilizing financial technology and investment planning. Investment decisions also show positive development, but there is still room for improvement in risk preparedness and alignment with personal financial goals. The results of the simple linear regression analysis show that financial literacy has a positive and significant effect on investment decisions among young people in Benjala Village.Based on these findings, it is recommended that young people improve their financial literacy, relevant institutions provide financial education programs, and future researchers expand the research scope to obtain deeper understanding of young people's investment behavior.